2003
DOI: 10.1589/jpts.15.71
|View full text |Cite
|
Sign up to set email alerts
|

SF-36 Health Survey in Disabled Sitting Volleyball Players in Japan

Abstract: We obtained and analyzed personal health and QOL of 145 players participating in the 2002 Japan Sitting Volleyball Goodwill Games in Hakuba, Japan. QOL was measured by the SF-36 Health Survey providing 8 specific categories of physical and emotional scores summarized into 2 main scores: the Physical Component Score (PCS) and Mental Component Score (MCS). There were 42 players with disabilities and 103 players without any disabilities. There were significant differences between the two groups of participants in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 4 publications
1
4
0
1
Order By: Relevance
“…Specifically, our results add depth to our understanding of the well-being of elite Paralympic sport athletes with quantitative data from a larger sample size relative to the modest sample sizes in previous research (e.g., Akasaka et al 2003;Dorogi et al 2008;Pensgaard et al 1999), and to the qualitative approaches typically found within the Paralympic sport literature (Smith and Sparkes 2012). Our data provides quantitative support of well-being strengths, and needs, previously reported through qualitative methods (Macdougall et al 2016).…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Specifically, our results add depth to our understanding of the well-being of elite Paralympic sport athletes with quantitative data from a larger sample size relative to the modest sample sizes in previous research (e.g., Akasaka et al 2003;Dorogi et al 2008;Pensgaard et al 1999), and to the qualitative approaches typically found within the Paralympic sport literature (Smith and Sparkes 2012). Our data provides quantitative support of well-being strengths, and needs, previously reported through qualitative methods (Macdougall et al 2016).…”
Section: Discussionsupporting
confidence: 77%
“…These scales are summarized into a Physical Health Component summary. The SF-36v2 has been shown to be valid (McHorney et al 1994;Ware Jr. et al 1994), has adequate internal consistency and test-retest reliability (Tsai et al 1997), and has been used to compare athletes with and without impairments (Akasaka et al 2003). …”
Section: Methodsmentioning
confidence: 99%
“…As a high-level competitive sport, sitting volleyball appeared on the international scene comparatively late, in 1980. That year sitting volleyball became an official event for the first time at the Paralympic Games in Arnhem, The Netherlands [6,7]. We follow the FIVB (Federation Internationale de Volleyball) rules, with additions from the WOVD (World Organization Volleyball for Disabled) rules and regulations for sitting volleyball.…”
Section: Introductionmentioning
confidence: 99%
“…We follow the FIVB (Federation Internationale de Volleyball) rules, with additions from the WOVD (World Organization Volleyball for Disabled) rules and regulations for sitting volleyball. Some characteristics of the game/court: the playing court is a 10 m by 6 m rectangle; the attack line is 2 m away from the center line axis; the net, which is 0.80 m by 6.50 m, is placed vertically over the center line and is 1.15 m high with regards to men's standards; players use hands for moving and sweeping on the court; buttocks must remain on the floor while playing the ball; block on the service is allowed; for official tournaments a classification on minimum disability is required [1,6,8].…”
Section: Introductionmentioning
confidence: 99%
“…Ao entender que a prática esportiva apresenta resultados importantes dentro do processo de reabilitação e da reinserção do individuo na sociedade (LABRONICI et al, 2000;AKASAKA et al, 2003), o esporte adaptado passa a receber maior visibilidade Rev. Educ.…”
Section: Introductionunclassified